La plénitude du vide et le vide de la plénitude: La représentation de l’espace dans Le square de Marguerite Duras et dans Tentative d’épuisement d’un lieu parisien de Georges Perec - Ila-Horváth, Zsófia (Verbum – Analecta Neolatina, 2014)
George Perec’s work and the oeuvre of Marguerite Duras are two closely related to topographies, which seem to be permeated by “vacuity”, both on the thematic and the formal level. Does the representation of space, the mise-en-scène of the decor have to be interpreted as part of what we could call the “writing of absence”, typical of the two writers? Or just the opposite, does the spatial dimension allow another interpretation of Perec’s and Duras’ work, respectively? In the present paper, we attempt to answer these questions by analysing the different methods used by the two writers to represent space.